Computational examination of non-darcian flow of radiative ternary hybridity casson nanoliquid through moving rotary cone - Wang, Fuzhang; Sajid, Tanveer; Muhammad Katbar, Nek; Jamshed, Wasim; Usman; Eid, Mohamed R.; Abd-Elmonem, Assmaa; Mohamed Isa, Siti Suzilliana Putri; Din, Sayed M El (Oxford University Press, 2023)
The goal of this research is to provide a novel conceptual base for ternary hybridity nanofluids that will improve heat transmission. This model illustrates how to produce heat conduction that is superior to the hybridity nanofluid. The ternary hybridity nanofluid is made by suspending three distinct kinds of nanostructures (TiO2, Al2O3, and SiO2) in ethylene glycol with varying physical and chemical linkages. The combination of these nanoparticles aids in the decomposition of hazardous compounds, environment cleansing, and the cooling of other equipment. This article describes the ternary hybrid nanofluids such as the conductivity of thermal and electrical, specific heat capacitance, viscosity, and density. The ordinary differential equations for the liquid and temperature are solved utilizing the Keller box method (KBM). The main finding discovered that the tri-hybrid nanofluid transferred more heat compared to the hybrid nanofluid. The velocity and temperature field diminishes for these ranges of parameters: 0≤ γ ≤2 (velocity slip γ⁠) and 0≤ γ1 ≤ 2 (temperature slip γ1) The Darcy–Forchheimer Fr ranges between 0.5≤ Fr ≤ 1.4 diminishes the fluid velocity. The fluid moving subjected to a rotating cone has various applications in engineering like cone clutch, steam generators, loudspeaker cooling, lubricating grease for seals, hydrology, geosciences, etc.